CSR Strategies of Five-Star Hotels in Denpasar-Bali Based on Local Community Perceptions - I Gusti Ayu Intan Saputra Rini; Muhammad Asyraf Hasim (Indonesian Journal of Sustainability Accounting and Management, 2021)
The hotel industry provides numerous jobs and has a significant contribution to local and global economies. Given that the hotel industry is an industry with a significant global impact, it is required to take social and environmental responsibilities earnestly. This study aims to describe the corporate social responsibility (CSR) strategies of five-star hotels in Denpasar City to examine the perceptions of surrounding communities toward these programs and to develop the appropriate CSR strategies for these hotels. This research is a qualitative study employing an exploratory sequential mixed method. The sample of hotel management staff who were interviewed and other respondents who filled out the research questionnaire were selected via purposive sampling. Results prove that CSR in five-star hotels in Denpasar City does not have its own autonomous field and budget authority. In fact, just one five-star hotel in the city has a CSR department. CSR activities in the hotels are in the form of maintenance and donations, and most of them (59%) are perceived as low by the surrounding community. Based on these findings, this work is able to develop a CSR management strategy for five-star hotels in Denpasar City.